A large deformation finite element analysis of uplift behaviour for helical anchor in spatially variable clay. (January 2022) - Cheng, Po; Liu, Yong; Li, Yu Ping; Yi, Jiang Tao
Abstract: Helical anchors are emerging as an innovative foundation design option for offshore applications to resist uplift loading. Numerous studies have been conducted to investigate the uplift behaviour of helical anchor under different helical bearing plate configurations in clay, using field or model tests and numerical analyses. However, almost all of them are limited to deterministic analyses, ignoring the influence of inherent spatial variability of soil. This work conducts a 3D large deformation random finite element analysis to examine the uplift behaviour of helical anchor in spatially variable clay. Both the stochastic and deterministic trends are reflected in the 3D non-stationary random field adopted. It is found that the spatial variability of soil strength significantly influences the failure mechanism of helical anchor. Parametric studies indicate that the coefficient of variation and vertical scales of fluctuation of soil strength can much influence on the uplift capacity, while the effect of horizontal scales of fluctuation is trivial. The goodness-of-fit test of probability distribution suggests that random uplift capacities follow log-normal distribution, whereby the relationship between factor of safety and probability of failure is established. The findings of this paper might facilitate the safety design of helical anchor.